Camarillo State Hospital Governor's Council Report - F.H. Garrett:::::: (1960)
This five page document is a governor's council report discussing the consultant service to the nursing department at Camarillo state hospital which a new procedural plan will occur in which training areas with review of our trainee curriculum teaching methods. Some of the methods that will be taught in this training are withdrawal patterns of schizophrenics, non-verbal communication with schizophrenics, bed-wetting, regression, and frustrations. All of these topic that will be covered in training hour is for staff to be better prepared in what they are doing.